Genotypic and phenotypic relationship in Burkholderia pseudomallei indicates colonization with closely related isolates - Son, Radu; Samuel, Lihan; Azhar, Idris; Oii, Wai Ling; Muthafar Husein, Al-Haddawi; Gulam, Rusul (UPM, 2000)
Seven isolates of Burkholderia pseudomallei from cases of melioidosis in human (2 isolates) and animal (2 isolates), cat (one isolate) and from soil samples (2 isolates) were examined for in vitro sensitivity to 14 antimicrobial agents and for presence of plasmid DNA. Randomly amplified polymorphic DNA (RAPD) analysis was used to type the isolates, using two arbitrary primers. All isolates were sensitive to chloramphenicol, kanamycin, carbenicillin, rifampicin, enrofloxacin, tetracycline and sulfamethoxazole-trimethoprim. No plasmid was detected in all the isolates tested. RADP fingerprinting demonstrated genomic relationship between isolates, which provides an effective method to study the epidemiology of the isolates examined.